A Critical Discourse Analysis on Beauty Product Advertisements - Susanti, Sri (Journal of Language Learning and Research (JOLLAR), 2019)
This research is aimed at describing the use of language in beauty ads (Pantene and Garnier ads), elaborating the way of the strategy are used in persuading the consumers and investigating the reason for the use of strategies. This is a descriptive qualitative method in which the data were collected from the advertisements of Pantene and Garnier. The collected data are the words, phrases, clauses, sentences that are used in ads. The data were analyzed according to Fairclough?s three dimensional approach of discourse analysis; they are textual features, discursive features, and social feature. The findings of this study show that the language used in Pantene and Garnier advertisements appear very interesting in building image to the audience and were successful in utilizing the various discourse strategies to gain people?s attraction to buy the product being advertised. For the social practices, the words found in their advertisement are considered have control or power over people.